2016
DOI: 10.1002/jbm.a.35823
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescent gelatin nanoparticles as imaging probes to monitor matrix metalloproteinase metabolism of cancer cells

Abstract: In this paper, autofluorescent gelatin nanoparticles were synthesized as matrix metalloproteinase (MMP) responsive probes for cancer cell imaging. A modified two-step desolvation method was employed to generate these nanoparticles whose size was controllable and had stable autofluorescence. As glutaraldehyde was introduced as the crosslinking agent, the generation of Schiff base (CN) and double carbon bond (CC) between glutaraldehyde and gelatin endowed these gelatin nanoparticles distinct autofluorescence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Due to low toxicity, organic nanoparticles have been vigorously developed as cell labels. However, the viability of the MCF‐7 cells decreased at 1.5 mg mL −1 of GelNPs, even it is a natural peptide/protein extractive from animal collagen . This study revealed that fPAANPs had LC50 of 6, 9, and 7.5 mg mL −1 in RAW264.7, HepG2, and Hepa1‐6 cells, respectively.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Due to low toxicity, organic nanoparticles have been vigorously developed as cell labels. However, the viability of the MCF‐7 cells decreased at 1.5 mg mL −1 of GelNPs, even it is a natural peptide/protein extractive from animal collagen . This study revealed that fPAANPs had LC50 of 6, 9, and 7.5 mg mL −1 in RAW264.7, HepG2, and Hepa1‐6 cells, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…With the unsatisfied NIRF of GTA‐crosslinked PAANPs, we investigated literatures, which told us that fluorescence produced by GTA crosslinking comes from two different kinds of double bonds, CN and CC . However, it was reported that GTA crosslinking produced visible fluorescence, which had already been used to fabricate autofluorescence organic nanoparticles . Nevertheless, no reports indicated that GTA crosslinking was used to manufacture NIRF nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the unreacted aldehyde terminals are neutralized with 10% glycine and the biocompatibility of cross-linked ESM is investigated using human HOS bone cells, which exhibit osteogenic potential [63][64] . Cell attachment on the ESM is observed by staining the nuclei of the cells since the strong autofluorescence of cross-linked gelatin limits the observation of the actin staining of the cells 65 Finally, the influence of BN concentration on osteoblast gene expression has been monitored by qPCR analysis (Figure 9c). Osteopontin (OSPN) gene expression is essential for bone mineralization.…”
Section: Cell Viability and Osteoblast Gene Expressionmentioning
confidence: 99%
“…In this work, the multifunctional GNPs were prepared with a modified method as we reported previously . Transmission electron microscopy (TEM) observation of the nanoparticles revealed a regular spherical shape with a size around 200 nm in diameter ( Figure a), and under dynamic light scattering (DLS) analysis, the gelatin nanoparticles were negatively charged, and the size of the gelatin nanoparticles was in a narrow distribution (Figure b and Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 87%